The Effect of Using Digital Learning Applications on Student Achievement in Elementary Schools - Asta, Ngr. Putu Raka Novandra; Aribowo, Aribowo; Saputra, Memed; Najmuddin, Najmuddin; Pahmi, Pahmi (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. Every digital technology will be able to influence its users. The response to incoming digital technology has pros and cons. The use of technology in education can no longer be avoided. The use of learning media in the form of applications will have a new impact on the world of education. Learning sometimes has to be done online due to some natural conditions that cannot be denied. Therefore, it is important to be able to use learning applications for education today. Purpose This study aims to determine the benefits of using learning applications. It is also useful to measure how influential the use of digital learning applications is on student achievement in elementary schools. The use of digital learning applications at the education level will have a significant impact on the success of education. Method. The method used in this research is a qualitative method. Qualitative method is a data that will be presented in the form of numbers. Data collection is in the form of distributing questionnaires to teachers and also parents whose children are at the elementary school level. In this case the statement is presented in google from. The statement contains matters relating to the influence of the use of digital learning applications on student achievement in education. This research is more focused on the elementary school level. Results. The results of this study explain that positive effects are obtained in the use of digital learning applications. However, there are also obstacles in using digital applications for learning at the elementary school level. Students who are still classified as underage must be extra supervised so as not to make mistakes in the use of technology. In addition, the use of technology that is influenced by the internet will also affect. This is due to some areas that are constrained by internet networks. In fact, there are still students in whose homes there is no digital technology. Conclusion This research can be concluded that the use of digital technology will have a significant and effective effect on student achievement at the elementary school level if done with the right method. Other supports are the internet and also tools as a medium to facilitate the use of learning applications. Every influence will certainly also experience challenges and obstacles as well as negative influences in its use.